2016
DOI: 10.1016/j.mri.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

A new NOE-mediated MT signal at around −1.6ppm for detecting ischemic stroke in rat brain

Abstract: In the present work, we reported a new nuclear Overhauser enhancement (NOE)-mediated magnetization transfer (MT) signal at around −1.6 ppm (NOE(−1.6)) in rat brain and investigated its application in the detection of acute ischemic stroke in rodent model. Using continuous wave (CW) MT sequence, the NOE(−1.6) is reliably detected in rat brain. The amplitude of this new NOE signal in rat brain was quantified using a 5-pool Lorentzian Z-spectral fitting method. Amplitudes of amide, amine, NOE at −3.5 ppm (NOE(−3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
132
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(150 citation statements)
references
References 45 publications
12
132
6
Order By: Relevance
“…Therefore, the absolute MTR asym (3.5ppm) signal intensity as well as the contrast of the ischemic stroke is reduced by the upfield NOE signals and the use of the asymmetry metric reduces the sensitivity of APT signals in ischemic stroke imaging. It should be mentioned that, contrary to our findings and the basic evidence from studies on cells and tissue (53) and high resolution NMR studies of proteins (56, 57), others have not found a change of relayed-NOE signals following acute stroke (29, 58, 59). The most likely explanation of this is a difference in saturation power B 1 , leading to very different contributions of fast and slow exchanging protons to the Z-spectrum (60).…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, the absolute MTR asym (3.5ppm) signal intensity as well as the contrast of the ischemic stroke is reduced by the upfield NOE signals and the use of the asymmetry metric reduces the sensitivity of APT signals in ischemic stroke imaging. It should be mentioned that, contrary to our findings and the basic evidence from studies on cells and tissue (53) and high resolution NMR studies of proteins (56, 57), others have not found a change of relayed-NOE signals following acute stroke (29, 58, 59). The most likely explanation of this is a difference in saturation power B 1 , leading to very different contributions of fast and slow exchanging protons to the Z-spectrum (60).…”
Section: Discussioncontrasting
confidence: 99%
“…Jones et al showed that in concentrated bovine serum albumin solution, both NOE and APT effects show pH dependence (Jones et al, 2013). On the other hand, Jin et al (Jin et al, 2013) and Zhang et al (Zhang et al, 2016) found very small NOE effect change following acute stroke. We would like to point out that Jones et al (Jones et al, 2013) used pulsed RF saturation scheme in volunteers and tumor patients, while Jin et al (Jin et al, 2013), Zhang et al (Zhang et al, 2016) and our study here used continuous wave saturation in acute ischemic animals.…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, Jin et al (Jin et al, 2013) and Zhang et al (Zhang et al, 2016) found very small NOE effect change following acute stroke. We would like to point out that Jones et al (Jones et al, 2013) used pulsed RF saturation scheme in volunteers and tumor patients, while Jin et al (Jin et al, 2013), Zhang et al (Zhang et al, 2016) and our study here used continuous wave saturation in acute ischemic animals. The differences in saturation schemes, diseases of interest, and the magnitude of pH change may partially explain the different conclusions of NOE contribution, which should be explored in the future.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Ideally, an imaging method as an analytical tool will not require the addition of MR contrast agents and will directly detect the injected material and its degradation profile. Chemical exchange saturation transfer (CEST) is a versatile MR imaging approach [22, 23] that can selectively visualize the distribution of specific proteins and metabolites in vitro [24], in vivo in animal models [25], and also in human brain [26, 27]. CEST acquisition is performed with an off-resonance saturation pulse, similar to magnetization transfer (MT), where contrast can be observed in a wide frequency range (~100kHz).…”
Section: Introductionmentioning
confidence: 99%